Determinants of Job Satisfaction on Turnover Intention Moderated by Internal Locus Control - Robin Robin; Chablullah wibisono; Bambang Satriawan (Goodwood, 2026)
Purpose: This study examines the influence of leadership, work motivation, work environment, work stress, and job insecurity on job satisfaction and its subsequent impact on turnover intention, with internal locus of control as a moderating variable, among employees of four-star hotels in Batam City. Methodology: A quantitative explanatory approach was used. Data were collected through a structured questionnaire from 343 respondents selected using a purposive sampling technique and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results: The work environment had the strongest effect on job satisfaction (? = 0.331), followed by work motivation and leadership, while work stress and job insecurity significantly reduced job satisfaction and increased turnover intention. Job satisfaction significantly lowered turnover intention and mediated the effect of the work environment, but the internal locus of control did not moderate the relationship. The model showed strong explanatory power (R² = 0.849, 0.805). Conclusions: Job satisfaction functions as a central mediator in reducing turnover intention, particularly through the work environment, underscoring the importance of job and personal resources in the hospitality industry. Limitations: This study is confined to four-star hotels in a single city and relies on cross-sectional, self-reported data, which limits causal inference and generalizability. Contributions: These findings provide empirical guidance for human resource management strategies in hospitality and extend organizational behavior and social exchange theories within the Indonesian context